Fenomena Tempat Hiburan Movi Box XDi Komplek Pertokoan Mall SKA Kota Pekanbaru Suatu Kajian Kriminologi: Universitas Islam Riau - Latief, Syahrul Akmal; Wallad, Mutia Soraya (Sisi Lain Realita, 2018)
As one of the big cities in Indonesia, the development of entertainment places in the city of pekanbaru growing each day. Starting from family karaoke until the cinema mini or known Movie Box. But many of Movie Box is pointed out as the place is misused to visitors do immoral. Freely in determining the Movies what to wact, and a various facilities that to make visitors comfortable and safe in the room. Additionally Movie Box also provide food and drinks to order. Interesting thing, this Movie Box design the room is very closed and the room lights can be turned off. In terms of supervision, nothing is done by the owner even CCTV was not available. Additionally the weak supervision of government make a Movie Box increasingly exist and a favorite young couple in pekanbaru.